Liberalisasi Dan Permasalahan Ekonomi: Sebuah Kritik Implementasi Ekonomi Islam Terhadap Ekonomi Pasar Bebas - Nur Fadilah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Islamic economics as an alternative solution in dealing with free markets awaits the role of Islamic economics in the era of globalization. Consumption, production and distribution in the Islamic (Islamic) view of the economy: bids for alternative solutions to consumption production. This research proves that in the discourse of Islamic economic criticism of free market and social economics is very strong, while there are many lawsuits and corrections to free market understanding. The idea of ​​transformation is needed to restructure economic understanding which prioritizes moral values ​​and human ethics, in achieving justice and prosperity. This author's conclusion states that in the discourse of Islamic economic criticism of the free market economy in the context of creating economic justice and social welfare, as conveyed by Muslim economists and structuralists. This research refutes the argument that was built by Islamic economic critical thinking on a free market economy based on the approach of individual interests and free competition in creating prosperity and justice for society.